2010
DOI: 10.1017/s1751731110000340
|View full text |Cite
|
Sign up to set email alerts
|

A sulfur amino acid deficiency changes the amino acid composition of body protein in piglets

Abstract: Experiments carried out to determine the amino acid requirement in growing animals are often based on the premise that the amino acid composition of body protein is constant. However, there are indications that this assumption may not be correct. The objective of this study was to test the effect of feeding piglets a diet deficient or not in total sulfur amino acids (TSAA; Met 1 Cys) on nitrogen retention and amino acid composition of proteins in different body compartments. Six blocks of three pigs each were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 26 publications
7
40
1
2
Order By: Relevance
“…Moreover, the reduction in protein content was moderate for both the muscles (6%), which is smaller than the 20% reduction in protein content of LM observed by Conde-Aguilera et al (2010) during a severe TSAA deficiency in weaned piglets. Skin sections were collected from five locations (i.e.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Moreover, the reduction in protein content was moderate for both the muscles (6%), which is smaller than the 20% reduction in protein content of LM observed by Conde-Aguilera et al (2010) during a severe TSAA deficiency in weaned piglets. Skin sections were collected from five locations (i.e.…”
Section: Discussioncontrasting
confidence: 56%
“…In this study, a deficient TSAA supply resulted in the use of both strategies by the animal and a Met deficiency of 19% resulted in a 15% reduction in ADG. In a previous study on weaned piglets with a short but more severe deficiency (40%), we observed a 20% reduction in ADG (Conde-Aguilera et al, 2010). Therefore, a prolonged and moderately deficient TSAA supply may have a proportionally greater effect on ADG than a short and severely deficient TSAA supply.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Possible reasons could be overestimated nutrient requirements, large safety margins in feeding recommendations or tissue-specific increased efficiency in using limiting resources. For instance, Conde-Aguilera et al (2010) reported that diets deficient or not in total sulphur amino acids had dissimilar impact on the amino acid composition of different body proteins in young piglets. However, to our knowledge, there is no recent information on the dynamics in empty body (EB) protein and lipid deposition of growerfinisher pigs fed diets restricted in CP or essential amino acid (EAA) during the whole growth period.…”
Section: Introductionmentioning
confidence: 99%